2011
DOI: 10.1902/jop.2010.100263
|View full text |Cite
|
Sign up to set email alerts
|

Development of an Animal Model for Aggregatibacter Actinomycetemcomitans Biofilm‐Mediated Oral Osteolytic Infection: A Preliminary Study

Abstract: Background Biofilm-induced inflammatory osteolytic oral infections, such as periodontitis and peri-implantitis, have complex etiology and pathogenesis. A significant obstacle to research has been the lack of appropriate animal models where the inflammatory response to biofilms can be investigated. The aim of this study is to develop a novel animal model to study the host response to Aggregatibacter actinomycetemcomitans (previously Actinobacillus actinomycetemcomitans)–biofilm colonizing titanium implants. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
85
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 48 publications
(85 citation statements)
references
References 44 publications
0
85
0
Order By: Relevance
“…This model allows standardized and reproducible quantities of viable bacteria to be formed as well-established biofilms on each implant, which we have previously demonstrated persists in vivo for several weeks after placement and causes infection, inflammation, and bone destruction locally. 31 …”
Section: Resultsmentioning
confidence: 99%
“…This model allows standardized and reproducible quantities of viable bacteria to be formed as well-established biofilms on each implant, which we have previously demonstrated persists in vivo for several weeks after placement and causes infection, inflammation, and bone destruction locally. 31 …”
Section: Resultsmentioning
confidence: 99%
“…We have demonstrated in previous work with the dental pathogen Aggregatibacter actinomycetemcomitans , that challenging a host with an already-established pathogenic biofilm results in greater ability of the pathogen to establish disease in an animal model of oral infection (Freire et al, 2011, 2017). While it is clear that being bound to DMs offers multiple advantages in terms of survivability and relative adherence to an epithelial target cell, the actual state of the DM-adhered L. reuteri and its phenotype has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Aa , or organisms likely to be Aa , have been isolated in high numbers from young patients with rapidly progressing alveolar bone breakdown . It has been shown that Aa can form a biofilm on titanium implants, which can in turn be used as a colonizing surface, allowing in vivo bacterial persistence and inflammatory host response . In addition, inflammatory cells, with B‐lymphocytes and plasma cells being the most dominant among them, infiltrate the connective tissue adjacent to the pocket epithelium.…”
mentioning
confidence: 99%